HUBUNGAN IMPLEMENTASI RELATIONSHIP MARKETING DENGAN LOYALITAS NASABAH PADA PT. BANK BRI SYARIAH KANTOR CABANG BENGKULU - Herfianti, Meiffa; Saputra, Diman Wido (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2018)
The purpose of this study is to determine whether there is arelationship between the implementation of relationship marketing with customer loyalty at PT. Bank BRI Syariah Branch Office of Bengkulu. This research uses qualitative and quantitative analysis, data collection method using questionnaire, tested by using rank spearman formula and hypothesis test. Based on the calculation of Spearman rank obtained correlation coefficient value of spearman rank or rho count (p) amount 0,765 is at the correlation interval 0,60 â?? 0,799 with strong criteria, meaning that the implementation of relationship marketing has a strong relationship with customer loyalty at PT. Bank BRI Syariah Branch Office of Bengkulu. Based on the hypothesis test of spearman rank correlation coefficient obtained t count 9,792 then the value of t arithmetic is compared with the value of t table at the level of confidence 95% or error rate 5% known value of t table is 1.66757 means that the value of t arithmetic greater than the value of t table (9,792 > 1,66757) then the hypothesis proposed in this study is acceptable means there is a significant positive relationship between variable relaionship marketing (X) with customer loyalty (Y) at PT. Bank BRI Syariah Branch Office of Bengkulu.